PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Mei Diah Putri Anggraeni (COMPETITIVE, 2020)
The purpose of this study is to determine the effect of profitability, liquidity, leverage on firm value and determine the effect of dividend policy in moderating the relationship of the effect of profitability, liquidity, leverage on firm value. This research is a quantitative research. The population is 154 manufacturing companies listed on the Stock Exchange in 2016-2018. The sampling method uses a purposive sampling method and a sample of 39 companies is produced. Analysis using multiple linear regression and MRA (Moderated Regression Analysis) using SPSS software version 24. The results showed that: 1) Profitability and leverage have a significant positive effect on firm value, while liquidity has no effect on firm value, 2) Dividend policy is able to moderate relationship between the effect of profitability on firm value, 3) Dividend policy is not able to moderate the relationship of the influence of liquidity on company value, 4) Dividend policy is able to moderate the relationship of the influence of leverage on firm value.